2004
DOI: 10.1007/s00127-004-0754-4
|View full text |Cite
|
Sign up to set email alerts
|

An RCT of early intervention in psychosis: Croydon Outreach and Assertive Support Team (COAST)

Abstract: The lack of clearly demonstrated improvements for COAST is consistent with the published literature so far. The fact that both groups improved in symptoms and functioning over the year suggests that while access to early intervention is helpful, community adult mental health teams should aim to offer high quality input at any stage of psychosis in order to meet client and carer needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 15 publications
3
70
0
4
Order By: Relevance
“…We excluded 3 studies that were nonrandomized, 18,27,28 4 studies in which less than 75% of the sample were FEP patients, [29][30][31][32] 4 studies with a follow-up shorter than 6 months, [33][34][35][36] and 2 long-term RCTs that did not report on relapse/readmissions, and the authors confirmed that further data were not available. 37,38 Nine of the included studies investigated psychosocial interventions, and 9 examined pharmacological treatments.…”
Section: Resultsmentioning
confidence: 76%
“…We excluded 3 studies that were nonrandomized, 18,27,28 4 studies in which less than 75% of the sample were FEP patients, [29][30][31][32] 4 studies with a follow-up shorter than 6 months, [33][34][35][36] and 2 long-term RCTs that did not report on relapse/readmissions, and the authors confirmed that further data were not available. 37,38 Nine of the included studies investigated psychosocial interventions, and 9 examined pharmacological treatments.…”
Section: Resultsmentioning
confidence: 76%
“…The idea of early intervention programs for schizophrenic patients includes not only early detection of disorders, but also multidisciplinary, com-prehensive care for patients and their families in the form of specialized pharmacological and non-pharmacological therapy: family interventions, behavioral cognitive therapy, social skills training, and problem solving, help with getting a job and extensive psycho-educational interventions for patients and their families. In 2010, Bird et al published a meta-analysis of several large controlled studies of early intervention in different centers around the world -COAST [93], LEO [94], OPUS [95], OTP [96], in which they demonstrated that during the first five years of illness, such early and widespread interventions have the advantage over standard care. Based on the results of this meta-analysis, early intervention in schizophrenic patients is believed to result in a clinically significant reduction in the risk of relapse and re-hospitalization.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…W 2010 r. Bird i wsp. opublikowali wyniki metaanalizy kilku dużych kontrolowanych badań na temat wczesnych interwencji w różnych ośrodkach na świecie -badania: COAST [93], LEO [94], OPUS [95], OTP [96], w której wykazali, że w okresie pierwszych pięciu lat trwania choroby takie wczesne i szerokie interwencje mają przewagę nad opieką standardową. Na podstawie wyników tej metaanalizy uważa się, że wczesna, kompleksowa interwencja u osób chorych na schizofrenię skutkuje istotną klinicznie redukcją ryzyka nawrotu choroby i ponownych hospitalizacji.…”
Section: Implikacje Terapeutyczneunclassified
“…En plus de contribuer à la diminution de symptômes négatifs, de symptômes psychotiques et de la toxicomanie, ils favorisent un engagement beaucoup plus marqué envers les services, une plus grande satisfaction des clients ainsi que des taux de suicide inférieurs à ceux des soins normaux (McGorry et coll., 2010 ;Nordentoft, Rasmussen, Melau, Hjorthoj et Thorup, 2014). Aucune différence significative n'a été constatée entre l'IP et les soins normaux dans un essai clinique randomisé dont la taille d'échantillon était très petite et dont les patients n'avaient peut-être pas commencé leur suivi dans un stade assez précoce (Kuipers, Holloway, Rabe-Hesketh et Tennakoon, 2004). Une méta-analyse a confirmé qu'une intervention intensive pendant les premiers stades de la psychose donnait des résultats cliniques (symptômes positifs et négatifs) et fonctionnels considérablement supérieurs à ceux des soins réguliers (Harvey, Lepage et Malla, 2007).…”
Section: éTudes Scientifiquesunclassified